Monozygotic twin discordance for phacomatosis cesioflammea further supports the post-zygotic mutation hypothesis. - Castori, M; Sarazani, S; Binni, F; Pezzella, F; Cruciani, G; Grammatico, P (2011)
Phacomatosis pigmentovascularis (PPV) is a group of sporadic skin disorders combining widespread cutaneous capillary malformations and pigmented nevi. Etiopathogenesis of the various forms of PPV is unknown, although a non-allelic twin spotting has been proposed as the most likely underlying mechanism. We report on the second instance of monozygotic twin discordance for PPV. Identical twins were observed shortly after birth, one affected by PPV and the other healthy, except for a standard Mongolian spot. Membrane examination was compatible with a monochorionic diamniotic pregnancy, and microsatellite analysis demonstrated monozygosity. This report confirms that PPV likely originates from a post-zygotic mutation rising shortly after conception and affecting different cell lineages. Speculations about mechanisms linked to phenotypic discrepancies among identical twins were also put forward.